294 Implementation of Colorectal Robotic Assisted Surgical Programme During a Global Pandemic: Collaboration Between Territorial and National Waiting Times Centre. (28th February 2022) - Hughes, R.; Massie, E.; Saldanha, J.; Komolafe, S.; Chapman, R.; Kirk, A.; Vella, M.; Moug, S.; MacArthur, C.; Mackie, H.
Abstract: Introduction: Golden Jubilee National Hospital (GJNH) established a thoracic Robotic Assisted Surgical (RAS) programme in 2018. In March 2021, GJNH invested in a new elective colorectal service and in response to the Scottish Government robotic investment established a collaboration with a territorial health board to host their robot and start a RAS colorectal programme. We provide an overview of barriers and facilitators leading to establishing this new collaboration. Method: An observational review of RAS training timeline. Demographics, surgical operations, and hospital length of stay were documented. Surgeons, perioperative team, management, and industry (Intuitive) were interviewed to provide insights into implementation and training. Results: Boards approved RAS business case in April 2021, robot on-site with GJNH governance approval in May. First cohort of colorectal surgeons completed proctored training July 2021. To date, 17 RAS resections performed (mean age 64, 9 males: 8 female). Mean length of stay 4.65 days. No anastomotic leaks and no mortality reported. Interviews revealed key facilitators: advantage of having an established RAS perioperative team and building on pre-existing industry links; developing and strengthening collaborative working between different health boards and surgeons. Barriers included: education of all team members to ensure patient safety for new specialty; multisite collaborative working. Conclusions: This work provides a template model for future RAS collaborations between different sites and health boards. Collaborative working in a green-hospital setting may improve equity of access for patients whilst future-proofing surgery against further waves of the pandemic.